2008
DOI: 10.1016/j.crhy.2008.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Coherent detection associated with digital signal processing for fiber optics communication

Abstract: Optical transmission systems have seen their performance (system capacity and system reach) drastically improved in the last 15 years by using new technologies such as wide band optical amplification, wavelength division multiplexing (WDM), dispersion management, introduction of 10 Gbit/s channel rate and now 40 Gbit/s, Differential Phase Shift Keying (DPSK) modulation. . . . In order to further increase system capacity while relaxing the constraints associated with higher channel rate (i.e. 100 Gbit/s), the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
(47 reference statements)
0
15
0
1
Order By: Relevance
“…Gaussian ASE noise was added at each in-line amplifier, for a (linear) received optical signal-to-noise ratio (OSNR) of 12 dB over 0.1 nm (e.g., giving BER ¼ 10 À5 in DQPSK at 10 Gbaud in the linear regime). [6,7] and PDM-QPSK [8,9,7,10] formats. LPF, low-pass electrical filter; DEC, decision block; LO, local oscillator; ADC, analog-digital converter; FIR, finite impulse response digital filter for GVD compensation.…”
Section: Single-channel Nsnimentioning
confidence: 99%
See 1 more Smart Citation
“…Gaussian ASE noise was added at each in-line amplifier, for a (linear) received optical signal-to-noise ratio (OSNR) of 12 dB over 0.1 nm (e.g., giving BER ¼ 10 À5 in DQPSK at 10 Gbaud in the linear regime). [6,7] and PDM-QPSK [8,9,7,10] formats. LPF, low-pass electrical filter; DEC, decision block; LO, local oscillator; ADC, analog-digital converter; FIR, finite impulse response digital filter for GVD compensation.…”
Section: Single-channel Nsnimentioning
confidence: 99%
“…Mach-Zehnder delay interferometers with one symbol delay T and balanced photo-detection are used for DPSK and DQPSK [6,7]. The digitalsignal-processing (DSP)-based coherent receiver for PDM-QPSK [7][8][9] uses a polarization beam splitter to split the polarizations of the incoming signal, and then the local oscillator is optically mixed with the signal in two optical hybrids (coherent mixers) followed by photo-detection, analog to digital conversion (i.e., sampling), FIR filtering for electronic group-velocity dispersion (GVD) compensation. Then clock recovery follows, and then electronic polarization demultiplexing and polarization-mode dispersion (PMD) mitigation is performed, usually with a constant-modulus algorithm (CMA).…”
Section: Introductionmentioning
confidence: 99%
“…The mix of data rates and modulation formats enables an average reduction of the network cost up to 15 %. Moreover, in [15], it is shown that the mix of data rates also reduces the energy consumption of an optical transport network from 10 to 77 %, depending on the considered fixed data rate.…”
Section: Performance Of Fixed and Flex-grid Networkmentioning
confidence: 98%
“…In the third type, the processing at all nodes may just be limited to 1R or 2R. Coherent detection is popular in wireless networks where improved data transfer rate and better quality are offered to optical systems (Charlet 2008). The optical modulation format has become a popular area of research to feed the coherent receivers.…”
Section: Background and Overviewmentioning
confidence: 99%